Analysis of Students’ Learning Outcomes Using Problem-Based Virtual Lab and Monopoly on Reaction Rates - Elisabeth Frenklin Pangaribuan; Ani Sutiani (Jurnal Inovasi Pembelajaran Kimia (Journal of Innovation in Chemistry Education), 2025)
Learning outcomes constitute a fundamental metric in assessing the effectiveness of the educational process, as they encapsulate students' comprehension, mastery, and practical application of the knowledge and skills imparted during instruction. Within the educational framework, these outcomes function not only as indicators of the efficacy of pedagogical approaches and instructional media but also as essential references for the continuous evaluation and enhancement of teaching quality. This research seeks to examine the learning outcomes of students who were instructed using Virtual Lab and Reaction Rates Monopoly media, both implemented through a Problem-Based Learning (PBL) model. The participants in this study were students from classes XI Bio I and XI Bio II at SMAN 18 Medan, selected through purposive sampling techniques. Data analysis was conducted using a one-tailed t-test at a significance threshold of Î± = 0.05. The findings revealed that: (1) the mean learning score of students engaged with the problem-based Virtual Lab was 80.22, whereas those using the problem-based Reaction Rate Monopoly media achieved an average score of 70.00; and (2) students exposed to the problem-based Virtual Lab media attained significantly higher learning outcomes compared to their counterparts who used the problem-based Reaction Rates Monopoly media.